PROFIL MOTIVASI BELAJAR SISWA SMP PADA PEMBELAJARAN DARING DI MASA PANDEMI COVID-19 - Vinna Agus Trianti; Siti Nurul Hidayati (PENSA: E-JURNAL PENDIDIKAN SAINS, 2021)
The research aims to objectively describe the learning motivation of junior high school students in online learning during the Covid-19 pandemic. The method used survey research. The research participants were students of SMP Negeri 1 Sumberrejo grade VII, VIII and IX totaling 90 students. The research instrument used was a learning motivation questionnaire sheet model of Attention, Relevance, Confidence, Satisfaction (ARCS), with a total statements of 20 numbers. Data collection techniques used through questionnaires distributed online via Google Form. The results of this research indicate that the level of student learning motivation in online learning at SMP Negeri 1 Sumberrejo in the ARCS aspect respectively is 66%, 73%, 64% and 69%. The conclusion of this research is that all of the students' learning motivation based on the ARCS aspect is still in the sufficient category. This also affects student learning outcomes where the level of completeness of student learning outcomes shows less well. This requires a more creative and innovative of online learning evaluations and in the use of technology media to increase student motivation during the Covid-19 pandemic.